Corrosion Inhibition Study of Mild Steel in Acidic Medium by Antibiotic Drugs: A Comparative Study - Md. A. Aziz, Md; Z. H. Khan, Mst S; Md. R. Hasan (Graduate Program of Syiah Kuala University, 2014)
Abstract - A comparison of the inhibiting efficiency of antibiotic drugs (ciprofloxacin, cloxacillin, and amoxicillin) on the corrosion of mild steel in 1 mol·L−1 HCl were studied at room temperature using mass loss measurement. The main reason is probably be due to the formation of protective coverage by the inhibitor as other authors reported previously. Adsorption characteristics of the inhibitor has also been studied using simple equation and it was found that drugs inhibits the corrosion of mild steel by being adsorbed on the surface of mild steel by a physical adsorption mechanism. The adsorption of drugs on the mild steel surface was found to be spontaneous and obey the Langmuir adsorption isotherm model. It was observed that the test drug has a promising inhibitory action in acid medium against corrosion of mild steel. Moreover it was revealed that an inhibition efficiency of 80.1 % can be achieved with 3×10-3M ciprofloxacin drug treatment on mild steel.Keywords: Steel corrosion; Antibiotic drugs; Adsorption isotherm; Inhibition mechanism.